The Effect of Shooting by Petanque Athletes of Bima Regency on the Achievement of Provincial Sports Week - Irfan; Nasrullah; Yanti, Sri (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. This study aimed to determine the extent to which the effect of shooting training using obstacles on athletes of the Petanque Training Center (TC) of Bima Regency could improve performance at the NTB Provincial Sports Week in 2023. Materials and methods. This research was a pseudo-experimental study with a